Identification of a novel recombinant polerovirus and other emergent viruses and tombusvirus-like associated RNA species associated with carrot motley dwarf disease in the United States - Erickson, Anna; Ter Horst, Anneliek M.; Carlson, Curtis R.; Falk, Bryce W.; Kuo, Yen-Wen (Frontiers in Microbiology, 2024)
Carrot motley dwarf (CMD) is a viral disease complex caused by co-infection of the polerovirus carrot red leaf virus with the umbraviruses carrot mottle virus or carrot mottle mimic virus, and/or a tombusvirus like associated RNA (tlaRNA), which depend on co-infection with a helper polerovirus to gain aphid transmissibility. In 2020 and 2021 carrot samples from Washington, United States (U.S.), and parsley and cilantro samples from California, U.S., exhibiting typical symptoms of CMD were submitted for diagnosis. Initial RT-PCR diagnostic assays identified the typical CMD viruses in the carrot samples, however only the umbraviruses and tlaRNAs were detected in the parsley and cilantro samples; as such, these samples were retested with another RT-PCR assay for generic polerovirus detection. Unexpectedly, the poleroviruses Torilis crimson leaf virus (TorCLV) and fennel motley virus were identified. Subsequent RNA sequencing analysis was conducted to confirm these results and look for other emergent viruses. In addition to confirming the diagnostic results, the recently described polerovirus Foeniculum vulgare polerovirus, the umbraviruses Pastinaca umbravirus 1 and wild carrot mottle virus, and the tlaRNA Arracacha latent virus E associated RNA were identified, making this the first report of these viruses and tlaRNA in the U.S. Using phylogenetic and pairwise identity comparisons and RDP4 recombination analyses, we also identified a putative novel polerovirus, for which we propose the name parsley polerovirus, that appears to be a recombinant between carrot polerovirus 1, sharing 92% amino acid (aa) identity with the RNA dependent RNA polymerase in the 5′ gene block, and TorCLV, sharing >98% aa identity with the capsid protein in the 3 gene block. This work adds to the growing list of polerovirus species exhibiting recombination between the 5′ and 3′ gene blocks, and highlights the unique, variable, and dynamic associations that can occur in polerovirus, umbravirus, and tlaRNA disease complexes.